User Interface and User Experience Analysis of Kejar Mimpi Mobile Application Using The User-Centered Design Method - Angela, Brigitha Valensia; Wulansari, Tina Tri; Riyayatsyah, Riyayatsyah; Fitrianto, Yuli; Rahim, Abdul (ILKOM Jurnal Ilmiah, 2023)
User criticism on the Play Store revealed some flaws in the Kejar Mimpi App review. Observations were made on research that discussed the Kejar Mimpi Application, and it discovered that no prior research on User Experience and User Interface had been conducted. Interviews will be conducted to collect additional data, and the initial questionnaire will be distributed on May 6, 2022. Developers and designers use User-Centered Design (UCD) design methodologies to ensure that the product or system meets the users' needs. This study used the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) methods or techniques to assess user interface and user experience. This research has produced as many as 24 design recommendations and a style guide. The final evaluation results measured using the SUS questionnaire increased the average value by 14,9% from a value of 67 (adjective rating Ok category, grade scale D, High Marginal category) to 77 (adjective rating Good, grade scale C, Acceptable category). The results of the UEQ also have gained an average increase in the ratio, where previously most were in below-average positions, now in good positions. Research on the user interfaces analysis and user experience of the Kejar Mimpi Application has the potential to be developed further. Therefore, the author has several suggestions that can be used for further research so that prototype part can be developed again to be more responsive and use different methods for evaluation of design results, such as Eye Tracking, Cognitive Walkthrough, and Heuristic Evaluation.